Tensile and impact properties of three-component PP/wood/elastomer composites - B. Pukanszky; G. Keledi; A. Sudar; K. Renner; Ch. Burgstaller; J. Moczo (eXPRESS Polymer Letters)
Polypropylene (PP) was reinforced with wood flour and impact modified with elastomers to increase stiffness and impact resistance simultaneously. Elastomer content changed in four (0, 5, 10 and 20 wt%), while that of wood content in seven steps, the latter from 0 to 60 wt% in 10 wt% steps. Structure and adhesion were controlled by the addition of functionalized (maleated) polymers. Composites were homogenized in a twin-screw extruder and then injection molded to tensile bars. Fracture resistance was characterized by standard and instrumented impact tests. The results showed that the components are dispersed independently of each other even when a functionalized elastomer is used for impact modification, at least under the conditions of this study. Impact resistance does not change much as a function of wood content in PP/wood composites, but decreases drastically from the very high level of the PP/elastomer blend to almost the same value obtained without impact modifier in the three-component materials. Increasing stiffness and fiber related local deformation processes led to small fracture toughness at large wood content. Micromechanical deformation processes depend mainly on the strength of PP/wood interaction; debonding and pull-out take place at poor adhesion, while fiber fracture dominates when adhesion is strong. Composites with sufficiently large impact resistance cannot be prepared in the usual range of wood contents (50–60 wt%).